Application of Android-Based Interactive Multimedia to Enhance Learning Outcomes in Understanding the Working Principles of SMAW Welding - Gustina, Hesti; Abdurrahman, Abdurrahman; Naryanto, Rizqi Fitri (Journal of Vocational and Career Education, 2024)
Traditional learning media remain prevalent due to the limited utilization of Android-based platforms among students as an instructional tool, necessitating an update in information delivery methods. The integration of technology in teaching materials aims to address this gap. This study seeks to implement Android-based interactive multimedia using the Problem Based Learning model to enhance students learning outcomes in understanding the working principles of Shielded Metal Arc Welding (SMAW) in cognitive, affective, and psychomotor domains. The research follows the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. The study involved 72 tenth grade students from the Welding and Metal Fabrication Engineering program, divided into control and experimental groups. The findings indicate that the application of Android-based interactive multimedia significantly increased students learning interest, with an initial average score of 63.194 rising to 73.889. T-test results revealed a significant difference between pre-test and post-test scores, with a significance value (2-tailed) of p = 0.00 < 0.05 and a t-value of 6.504. The hypothesis testing confirms that the use of Android-based interactive multimedia positively influences the learning outcomes of tenth grade students in the Welding and Metal Fabrication Engineering program at SMK Negeri 1 Adiwerna. Based on these findings, it can be concluded that the implementation of Android-based interactive multimedia effectively enhances students understanding of SMAW welding principles.